Signs of Crime Introducing Forensic Semiotics - Danesi, Marcel (De Gruyter, 2013)
This book will introduce the field of forensic semiotics as a tool for understanding crime and criminality. It will focus on how symbolism, ritual, and other sign-based activities play a crucial role in the constitution of criminal organizations and often in the enactment of individual crimes. It will present semiotic notions, methods, and techniques that can be applied to forensic science, such as the role of ritual and slang in criminal gangs.- Resumé vydavatel
Keywords: kriminalita; forenzní vědy; sémiotika; crime; forensic sciences; semiotics; elektronické knihy; monografie; electronic books; monographs